Efektivitas Ruang Publik Terpadu Ramah Anak (RPTRA) - Putra Perdiansyah; Dinar Sugiana Fitrayadi; Qotrun Nida (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
This research was conducted with the aim offind out how much the level of effectiveness of Child-Friendly Integrated Public Spaces (RPTRA). This research uses a descriptive research type and a quantitative approach. This research is located in a number of Child-Friendly Integrated Public Spaces (RPTRA) located in Rawa Buaya Village, Cengkareng District, West Jakarta City. The population in this study were the people of Rawa Buaya Village aged 10-64 years who were taken 100 people to be used as research samples using simple random sampling. The data collection technique used was a closed questionnaire using a Likert scale. The validity and reliability calculations were calculated using SPSS Version 26 and the effectiveness measurement was calculated using the Likert Summarting Rating (LSR) formula with the help of SPSS Version 26. The results of this study found that the RPTRA effectiveness level reached 75.3%. With an effectiveness level of >65% according to the research hypothesis, therefore it can be said that Child-Friendly Integrated Public Spaces (RPTRA) as a policy of the DKI Jakarta Provincial Government as a step towards realizing DKI Jakarta as a Child Friendly City have been fairly effectively implemented.